2D common‐offset traveltime based diffraction enhancement and imaging. (19th August 2013) - Asgedom, Endrias G.; Gelius, Leiv ‐J.; Tygel, Martin
ABSTRACT: The diffracted energy in a seismic recording contains key information about small‐scale inhomogeneities or discontinuities of the subsurface. Diffractions can therefore lead to high‐resolution imaging of subsurface structures associated with hydrocarbon traps. However, seismic diffracted signals are often much weaker than specular reflections and consequently require enhancement before they can be utilized. In this paper diffractions are enhanced relative to reflections based on two traveltime techniques, namely the modified common‐reflection‐surface approach, which uses the common‐reflection‐surface technique with some modification to tailor it for diffractions and the replacement‐media approach derived here for the purpose of a simplified parametrization of diffraction traveltimes. Both approaches are implemented in the common‐offset domain with the use of a finite‐offset central ray unlike the zero‐ or small‐offset diffraction enhancement techniques that use a zero‐offset central ray. The validity of the two moveout expressions is tested using velocity data taken from a smooth isotropic Marmousi model. A feasibility test was also carried out with respect to the new replacement‐media traveltime approximation addressing the various effects of signal‐to‐noise ratio, depth and lateral displacement of the diffractor location. Finally, diffraction enhancement and imaging was performed on 2D seismic data from the Jequitinhonha basin offshore Brazil. Diffractions were significantly enhanced and a high‐resolution image of the discontinuities of the subsurface was obtained.